Dutch students' evaluations of EMI and L1MOI lectures: The role of non-native pronunciation. (August 2022) - Hendriks, Berna; van Meurs, Frank
Abstract: In a within-subjects experiment, 119 Dutch listeners evaluated authentic English and Dutch lecture fragments recorded by the same Dutch lecturer. For each fragment, they answered multiple-choice comprehension questions and rated the lecturer on comprehensibility, attitudinal measures (status, competence, likeability and dynamism), and perceived teaching quality. Findings showed that actual comprehension was not different for the English and the Dutch fragments. The lecturer was evaluated less positively in the English fragments than in the Dutch fragments in terms of status, competence, dynamism and teaching quality, but not likeability. A mediation analysis showed that language choice had no direct effect but only indirect effects on perceived teaching quality through comprehensibility and non-native pronunciation. Our study shows that the use of EMI instead of L1MOI would not appear to result in reduced comprehension but does result in more negative perceptions of the lecturer, and that non-native pronunciation contributes to these perceptions.